Caracterização da paisagem do município de Roque Gonzales-RS: potencialidades e fragilidades - Lima, Thiane Kist de (2023)
The landscape is an element configured by biophysical and cultural dynamics, where the main transformative agent is the human being. The river, in turn, can be considered as one of the structuring elements of the landscape that suffers most from the artificialization caused by human action. Given this, initially, this research proposes to explore the landscape of the municipality of Roque Gonzales-RS, considering the influence of the implementation of the Passo São João Hydroelectric Plant in its territory, through a brief temporal analysis – before and after the project. Subsequently, the landscape units will be identified and the attributes of the municipality's landscape will be characterized, evolving the understanding of its potentialities and weaknesses. With the use of geotechnology tools, the landscape will be spatialized, and based on multi-criteria analysis methodologies and the analytical classification process, the emerging environmental fragility of the study landscape will be released. Finally, the results of the multimethods will be triangulated for analysis and development of guidelines. This study seeks to provide subsidies for the preparation of catalogs and landscape charts for the municipality, and also for the ecological planning of the landscape.